Adaptation to the waste anesthesia gas system: Gaps in knowledge and opportunities for positive environmental impact (Journal of Advanced Veterinary and Animal Research, 2015)
Canisters containing activated charcoal are commonly used  in  the  laboratory  setting  to  collect  waste anesthetic gas (WAG). This requires the weighing of the WAG canister after each use and for investigators to  maintain  an  accurate  time  log  of  anesthesia duration.  A  typical  rodent  anesthesia  station  may include  the  use  of  3  WAG  canisters;  one  for  the anesthesia induction box, one for the operative table, and  one  for  gas  monitoring.  To  simplify  the anesthesia breathing circuit, we have developed a T connector that replaces the need for having multiple WAG  canisters.  The  T  connector  directs  the  waste anesthetic  from  multiple  sources;  the  anesthesia induction box, operative table and gas monitor into a single  WAG  canister.  Use  of  the  T  connector appears  to  be  a  safe,  acceptable  device  that conveniently  directs  waste  gas  while  improving charcoal  adsorption  within  the  canister.  In  addition, this  device  may  have  a  positive  impact  on  the environment  with  a  secondary  benefit  of  possible cost  savings  associated  with  the  purchase  and disposal of the hazardous waste contents. http://dx.doi.org/10.5455/javar.2015.b106